Substantiation of the use of innovative physical therapy tools in the Armed Forces of Ukraine with myofascial pain syndrome due to long-term use of personal protective equipment - Danko, Daryna; Yudenko, Oksana (The Ukrainian Scientific Medical Youth Journal, 2024)
at the present stage of development of the health care system, the awareness of pain pathology as a typical problem of different segments of the population leads us to the understanding that a significant place in its formation and development is given to the theory of psychogenic recovery, which is studied by psychosomatic medicine and requires comprehensive therapeutic intervention. One of the main factors is the difference in the reaction of its strength, or the absence of pain due to emotional stress, in different parts of the body. In the context of Russia’s full-scale invasion, the issue of correction and restoration of the physical and functional state of the musculoskeletal system of servicemen with myofascial pain syndrome, in particular, which occurs as a result of prolonged use of personal protective equipment, is of great importance. From today’s perspective, myofascial pain syndrome is characterised by the presence of specific muscle pain. The pain sometimes radiates to another part of the body, not coinciding with its direct source. The pain syndrome is characterised by the presence of trigger points - localised hypersensitive bands in the muscle or fascia that can reproduce specific pain during palpation. Accordingly, this requires the use of effective means of complex physical therapy, both classical and innovative, which will allow for the highest quality restoration of the personnel’s performance and combat capability after performing assigned tasks or solving daily professional tasks in extreme conditions. We believe it is important to raise the level of theoretical awareness of modern physical therapy tools. This will contribute to a quantitative and qualitative reduction in the manifestations of pain in the process of overcoming its consequences of various localisation in military personnel as a result of long-term use of personal armour protection.